Basinwide water management: A spatial model - Ujjayant Chakravorty; Chieko Umetsu (Fondazione Eni Enrico Mattei (FEEM), 2000)
This paper develops a spatial model for a water basin that allows for surface water allocation and re-use of the water that is lost. The analytical solution suggests specialisation of production over space - upstream farmers use canal water and downstream farmers pump groundwater that is lost upstream. Groundwater emerges as an endogenous "backstop." The empirical results suggest that when traditional conservation technologies are used, optimisation over the entire basin leads to significant increases in aggregate output, project area and water use. Somewhat counter-intuitively, rents from water decrease if farmers switch from traditional to modern irrigation technology.
Keywords: Q25; Q15; R30; 330; Water allocation; spatial models; conjunctive use; irrigation technology; Bewässerung; Grundwasser; Allokation; Theorie